2022
DOI: 10.15386/mpr-2278
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alzheimer’s disease and periodontitis - a systematic review and meta-analysis of evidence from observational studies

Abstract: The relationship between periodontitis (or periodontal disease) with Alzheimer’s disease has been reported by various primary sources in the past decade, but not with a solid secondary research statement. A systematic review and meta-analysis was conducted in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and registered (Reference number: CRD42020185264) with PROSPERO (International prospective register for systematic reviews). A lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…As cognitive decline may also lead to poor periodontal health, reverse causality may confound the association. 39 , 40 To account for this, only longitudinal studies were included. 41 For dementia as an outcome, studies were restricted to dementia‐free participants at baseline, and an additional meta‐analysis was conducted restricting each main model (Figure 3A–E ) to studies with ≥10 years of follow‐up (Figure S4 A–E).…”
Section: Methodsmentioning
confidence: 99%
“…As cognitive decline may also lead to poor periodontal health, reverse causality may confound the association. 39 , 40 To account for this, only longitudinal studies were included. 41 For dementia as an outcome, studies were restricted to dementia‐free participants at baseline, and an additional meta‐analysis was conducted restricting each main model (Figure 3A–E ) to studies with ≥10 years of follow‐up (Figure S4 A–E).…”
Section: Methodsmentioning
confidence: 99%
“…There is rising evidence for an association between intraoral inflammatory conditions and AD [ 17 , 18 , 19 ]. More than 50% of all people over the age of 35 worldwide are affected by periodontitis, and approximately 10–15% suffer from a severe form of the disease which can lead to the loss of dentition [ 333 ].…”
Section: Individual Approachesmentioning
confidence: 99%
“…Such a relationship is also discussed for dementia, especially AD, and the intraoral condition, which may be bidirectional: on the one hand, the reduction in memory capacity caused by AD is certainly causal for the decrease in personal oral hygiene ability and thus ultimately for the increase in the risk for the development of caries and periodontitis [ 341 , 342 ]. On the other hand, there is evidence that periodontitis itself and the associated microbial colonization and inflammatory response is associated with AD [ 18 , 19 , 343 , 344 ].…”
Section: Individual Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies(Holmer, Eriksdotter, Schultzberg, Pussinen, & Buhlin, 2018), periodontitis has been shown to be an important risk factor for Alzheimer's disease. The results of cross-sectional and longitudinal studies have shown (Fu et al, 2022;Kaliamoorthy et al, 2022), periodontitis is strongly associated with cognitive impairment (CI) and Alzheimer's disease (AD). In addition, studies on AD patients from patients with periodontitis and human animal models have shown (Ilievski et al, 2018), Porphyromonas gingivalis (Pg) and/or its product gingival protease were transferred to the brain.…”
Section: Introductionmentioning
confidence: 99%